Empirical Evidence on the Role of Local Own-Source Revenue in Strengthening Fiscal Independence of Indonesian Local Governments - Nurhany Hasanah; Rahma Masdar; Andi Chairil Furqan; Tenripada (Owner : Riset dan Jurnal Akuntansi, 2025)
Regional fiscal independence is a key indicator of local governments’ ability to manage development sustainably without excessive dependence on central transfers. However, many regions in Indonesia still face limited fiscal capacity, primarily due to suboptimal management of Local Own-Source Revenue (PAD). This study aims to analyze the influence of each PAD component regional taxes, retributions, proceeds from regional asset management, and other legitimate PAD on regional fiscal independence in Indonesia. The research uses secondary data from 542 provinces, regencies, and municipalities during the 2019–2023 period, with 2,485 observations obtained through purposive sampling. Data were analyzed using panel data regression with the Fixed Effects model in STATA 17. The results show that all PAD components have a positive and significant effect on regional fiscal independence, indicating that greater PAD optimization strengthens local financial autonomy. The findings suggest that local governments should manage PAD professionally and strategically to improve institutional capacity, enhance revenue governance, and reduce dependence on central government transfers. In conclusion, strengthening PAD serves as the foundation for sustainable fiscal independence and long-term regional development.